Collectie Bo Boustedt. - Palme, Per (Amsterdam : Stedelijk Museum Amsterdam, 1964)
Adams, Robert ; Armitage, Kenneth ; Arp, Hans (Jean) ; Avramidis, Joannis ; Bennazzi, Raffael ; Berg, Christian ; Bill, Max ; Butler, Reg ; Calder, Alexander ; César ; Chadwick, Lynn ; Chillida, Eduardo ; Consagra, Pietro ; Couzijn, Wessel ; Delahaye, Charles ; Gabo, Naum ; Ghermandi, Quinto ; Giacometti, Alberto ; Gilioli, Emile ; Heerup, Henry ; Hepworth, Barbara ; Hoflehner, Rudolf ; Holmgren, Martin ; Ipousteguy, Jean ; Jacobsen, Robert ; Jones, Arne ; Kemeny, Zoltan ; Lardera, Berto ; Laurens, Henri ; Marini, Marino ; Meier-Denninghoff, Brigitte ; Minguzzi, Luciano ; Moore, Henry ; Mooy, Jaap ; Negri, Mario ; Nevelson, Louise ; Noguchi, Isamu ; Öhrström, Edvin ; Paolozzi, Eduardo ; Pernevi, Allan Axel ( Palle ) ; Richier, Germaine ; Somaini, Francesco ; Stankiewicz, Richard ; Tajiri, Shinkichi ; Wotruba, Fritz
Collectie Bo Boustedt, Stedelijk Museum Amsterdam, 01.05. - 07.06.1964
Nederlands
kunstcatalogus